De Lost in Austen à Lost Austen ? Une réflexion sur l’élaboration d’une fiction transfuge - Claire Colin (Itinéraires)
This paper deals with the four-part 2008 British television series Lost in Austen, written from a Guy Andrews’s screenplay and directed by Dan Zeff, as an adaptation of the popular Jane Austen’s novel Pride and Prejudice. Instead of being a simple recreation which would be characterized by nonsense, this series can rather suggest a reflection about how to create an “escapist fiction,” according to the Richard Saint-Gelais’s phrase (here translated). The author of Fictions transfuges, la transfictionnalité et ses enjeux thus labels the fictions created from a first fiction but with enough autonomy, like, for example, the fanfictions. Indeed, Lost in Austen seems first included in a large Austenian fictional world, where the love stories are the most important. But, as the series goes on, it develops its own world, always with the original novel’s stamp but this reference gradually becomes secondary.